Morphological Changes Related to Adherence Properties of Selected East Coast Malaysia Condiments on Dentine Pulp Tissues Preparations. - Che Ghazali, Farid; Wan Muda, Prof Dr Wan Abdul Manan; MatAsan, Jamaruddin (2003)

(untitled)
Local condiments consumption is a key constituent of diets throughout the east coast of Peninsu1ar Malaysia. Little evidence-based knowledge is known of the morphological changes that may impinge on oral health due to consumption of these local condiments.